2018
DOI: 10.1177/0033294118773400
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Implicit Leadership Theories, Leader–Member Exchange, Self-Efficacy, and Attachment Theory to Predict Job Performance

Abstract: The impact of implicit leadership theories on performance and the mechanism linking them have received insufficient theoretical and research attention. Drawing on Bandura's social cognitive theory, the present study contributes theory through examining the assertion that higher congruence between followers' implicit leadership theory and the characteristics of supervisors enhance job performance through higher quality of leader-member exchange and self-efficacy. Moreover, in the proposed model, attachment inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 105 publications
1
29
0
2
Order By: Relevance
“…Previous researches in the related field indicated that employees’ work outcomes can be reinforced by a high-quality relationship with their supervisor (Kim and Koo, 2017; Klein and Kim, 1998). Khorakian and Sharifirad (2018: 17) discussed LMX and performance together in their study and they considered that self-efficacy as social-cognitive structure plays as a bridge on the gap between LMX and performance. On the other hand, few studies report nonsignificant relationships between LMX and work outcomes (Scandura and Pellegrini, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous researches in the related field indicated that employees’ work outcomes can be reinforced by a high-quality relationship with their supervisor (Kim and Koo, 2017; Klein and Kim, 1998). Khorakian and Sharifirad (2018: 17) discussed LMX and performance together in their study and they considered that self-efficacy as social-cognitive structure plays as a bridge on the gap between LMX and performance. On the other hand, few studies report nonsignificant relationships between LMX and work outcomes (Scandura and Pellegrini, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our findings propose when creativity is supreme, the employee should be conscious of the expectations they hold on themselves, which shape their creative thoughts. Such cognitions are particularly crucial in modern organizations where the employee keep low expectations for their creativity (Khorakian & Sharifirad, 2019). Though other factors may take part, our findings point out that the employees' self-beliefs and hierarchical position stimulate or suffocate their creative effort in the organization.…”
Section: Practical Implicationsmentioning
confidence: 69%
“…When ILTs were used in applied settings to determine their impact on various organizational outcomes, researchers measured them either directly, by asking participants about the degree to which their leaders possess specific ILTs traits (e.g., Khorakian & Sharifirad, 2019) or indirectly, by measuring two sets of ILTs traits, one representing participants' expectations from ideal leaders and a parallel one, assessing recognition of those ILTs traits in their actual leaders (e.g., Biermeier-Hanson & Coyle, 2019). In the second case, researchers computed a congruence score, underpinning the ideal-actual match, which they used to predict various outcomes.…”
Section: Ideal-actual Ilts Congruencementioning
confidence: 99%